Перчатки Ариадны: [для среднего школьного возраста] / Анна Летягина ; [художник Диана Лапшина] - Летягина Анна (Страшилки, 2021)
Экземпляры: 21 (20220303) / Инвентарный номер: 67701 / Цена: 253.00 / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: Л 52 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=411.2)6-4